Reasons for excluding adverse events in cost-effectiveness analyses of vaccines: A survey amongst authors - Luyten, Jeroen; van Hoek, Albert Jan (Vaccine, 2025)
Although vaccines must adhere to the strictest safety standards in medicine, adverse events (AE) do occur occasionally. Even when clinically negligeable, these AE can still have health-economic implications, affecting the cost-effectiveness of vaccines. A review revealed that only 25 % of recent health-economic studies on childhood vaccines incorporated AE. In this study, we reached out to all corresponding authors of the reviewed articles who excluded AE to understand their rationale for exclusion (response rate 40 % (27/67)). The predominant reasons for not including AE were (1) that these were deemed too rare and insufficiently relevant (17/27, 65 %), (2) analysts adhered to previous methodologies that excluded AE (10/27, 35 %) and (3) there was a lack of sufficient data (9/27, 33 %). We argue that AE deserve more attention from analysts and that more efforts are needed to develop conceptual methods and collect data that enable meaningful incorporation in CEAs. •AE are excluded from most economic evaluations of (childhood) vaccines.•We investigated the reasons behind exclusion in a sample of authors of recent studies.•The most important reason stated was that AE were deemed to be irrelevant for cost-effectiveness.•We argue that AE can be an important factor of cost-effectiveness and must be analysed.•More research is needed to collect better data to enable a meaningful quantification of AE.